2005
DOI: 10.1002/maco.200403849
|View full text |Cite
|
Sign up to set email alerts
|

A case of nitridation, carburization and oxidation on a stainless steel

Abstract: A case of corrosion was studied on stainless steel tubes, exposed to a nitriding, carburizing and oxidizing environment (mainly NH 3 and CO 2 ) at 390 -450 8C. Due to the high nitriding potential prior formation of internally nitrided layers occurs, at higher temperatures (> about 425 8C) under precipitation of CrN in the layer and at lower temperatures under formation of the c N -phase, i.e. austenite with high N-content and expanded lattice. The latter process causes more severe corrosion, due to the high ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 26 publications
(11 reference statements)
0
12
0
Order By: Relevance
“…Only when the nitriding temperature was increased to 400°C, were Cr nitrides formed, so although they are thermodynamically stable, there can be a kinetic driving force to their formation. Similarly, precipitation of Cr nitrides was not observed (<425°C) for an 18% Cr stainless steel exposed to NH 3 + CO 2 gas mixtures . That no alloying element nitrides could be observed on the grate tube investigated, could therefore be due to the low temperature where only interstitials can be expected to have significant mobility and not the larger metal atoms.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Only when the nitriding temperature was increased to 400°C, were Cr nitrides formed, so although they are thermodynamically stable, there can be a kinetic driving force to their formation. Similarly, precipitation of Cr nitrides was not observed (<425°C) for an 18% Cr stainless steel exposed to NH 3 + CO 2 gas mixtures . That no alloying element nitrides could be observed on the grate tube investigated, could therefore be due to the low temperature where only interstitials can be expected to have significant mobility and not the larger metal atoms.…”
Section: Discussionmentioning
confidence: 81%
“…Experiences from the ammonia industry indicated that nitriding occurs above 380°C for ferritic steels and increased with temperature, but also that nitriding increased by a factor of 3–5 when high stresses were applied. Investigation of a 304‐L stainless‐steel heat exchanger in a catalytic reactor (NH 3 + CO 2 ) at 390–450°C also revealed nitridation, carburisation, and oxidation . A high nitrogen and carbon content was linked to Vickers hardness values of >1,000 HV and spallation of brittle corrosion products which has not been a problem for the 15Mo3 grate but could be a problem with increase in alloying elements.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Studies of chromium nitride films formed by ion beam-assisted deposition also suggest that CrN is the stable phase when excess nitrogen is present [8]. Cr undergoes rapid nitridation compared to carburisation, and the nitride phase is more stable than the carbide [9] (particularly under high [N] plasma conditions). This is consistent with our samples where the CrN signature never has any associated carbon signal.…”
Section: Resultsmentioning
confidence: 99%
“…The large amount of ammonia in the gas phase ensures many nitrogen radicals (NH y , with 0 < y < 2) which induce nitridation of FeCr x , leading to the precipitation of CrN. In the well-studied process of nitridation of bulk stainless steels [9], such precipitation leads to internal stress in the material [10]. For nanoscale particles this stress can be relieved through segregation of the Fe and CrN.…”
Section: Discussionmentioning
confidence: 99%